2004
DOI: 10.1038/sj.bjp.0705794
|View full text |Cite
|
Sign up to set email alerts
|

NO and KATP channels underlie endotoxin‐induced smooth muscle hyperpolarization in rat mesenteric resistance arteries

Abstract: 1 Smooth muscle membrane potential and tension measurements were made in isolated mesenteric resistance arteries from rats exposed to bacterial endotoxin (lipopolysaccharide, LPS; 10 mg kg À1 , i.p.) for 3 h to mimic septic shock syndrome. 2 Over this period, rats developed an endotoxaemic response, assessed in vivo as a 4174 mmHg drop in mean blood pressure, vascular hyporeactivity to noradrenaline (1 mg kg À1 , i.v.) and a significant increase in core body temperature. 3 In mesenteric small resistance arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
8
1
Order By: Relevance
“…A recent study looking at membrane potential in endothelial cells showed that responses induced by acetylcholine were even shorter in duration when ouabain was added, implicating a role for Na ϩ -K ϩ -ATPase in the maintenance of response (5). It has been reported that NO can cause hyperpolarization of vascular smooth muscle (12,38) through its direct actions on ATP-sensitive K ϩ channels (4,40). However, our data found only a small and statistically insignificantly different contribution of NO to hyperpolarization.…”
Section: Discussioncontrasting
confidence: 56%
“…A recent study looking at membrane potential in endothelial cells showed that responses induced by acetylcholine were even shorter in duration when ouabain was added, implicating a role for Na ϩ -K ϩ -ATPase in the maintenance of response (5). It has been reported that NO can cause hyperpolarization of vascular smooth muscle (12,38) through its direct actions on ATP-sensitive K ϩ channels (4,40). However, our data found only a small and statistically insignificantly different contribution of NO to hyperpolarization.…”
Section: Discussioncontrasting
confidence: 56%
“…The endothelium-free rings were prepared by gently rubbing with a sanded polyethylene tube and confirmed with vasodilation response to acetylcholine. The isolated mesenteric arteries were transferred to icecold Krebs solution containing NaCl 118.0, NaHCO 3 25.0, KCl 3.6, MgSO4 1.2, KH2PO4 1.2, glucose 11.0, CaCl2 2.5 in mM (42). A ring segment 2 mm in length was mounted on a force electricity transducer (model FT-302; iWorx/CBSciences, Dover, NH) in a tissue bath with 5 ml Krebs solution.…”
Section: Methodsmentioning
confidence: 99%
“…Nitric oxide was also shown to hyperpolarize SMCs in rabbit mesenteric arteries via a mechanism that involves cGMP and activation of K ATP channels (1040). Hyperpolarization induced by NO was also shown to involve K ATP channels in mesenteric SMCs (1547). K ATP channels have also been implicated in vasodilation induced by NO in several other systems (57, 581).…”
Section: Katp Channelsmentioning
confidence: 99%